Students' Perception of Learning English Vocabulary Via @Kampunginggrism Instagram Account - Hasbi, Muhamad; Cahyaningsih, Apriliana Dwi (LinguaEducare: Journal of English and Linguistic Studies, 2024)
This research seeks to explore students' perceptions of learning English vocabulary through the @kampunginggrism Instagram account and to detail how the platform enhances their vocabulary. The study uses a descriptive qualitative approach, focusing on six eighth-semester students from the English Education Department at Salatiga State Islamic University (UIN Salatiga). Data was gathered via observation, interviews, and documentation.The findings reveal that the @kampunginggrism Instagram account is a highly effective tool for improving students' English vocabulary. It provides an engaging and accessible way to learn, making the experience enjoyable and easy for students. The account is recommended as a valuable resource for other students looking to enhance their English vocabulary. Through features such as quizzes, the platform encourages active participation, helping students to look up unfamiliar words and apply new vocabulary. Overall, the account offers a range of tools that make vocabulary learning fun, efficient, and impactful.